Chronic obstructive pulmonary disease [computer file] an overview - Barnes, Peter J. 1946-.; Focus Medica (Singapore Focus Medica, 2007)
"Chronic obstruction of the flow of air through the airways and out of the lungs is very often irreversible. People having this condition suffer from chronic bronchitis or emphysema and are said to have chronic obstructive pulmonary disease or COPD. Presentation describes the respiratory system, its function, the disease, its causes, diagnosis and complications. It also explains the treatment options and self-care in detail."
"Multimedia presentation in medical animation."
Keywords: Lungs -- Diseases, Obstructive -- Interactive multimedia; Lungs -- Diseases, Obstructive -- Diagnosis -- Interactive multimedia; Lungs -- Diseases, Obstructive -- Treatment -- Interactive multimedia